The Hidden Curriculum of Monolingualism: Understanding Metonymy to Interrogate Problematic Representations of Raciolinguistic Identities in Schoolscapes - Przymus, Steve Daniel; Huddleston, Gabriel (International Journal of Multicultural Education, 2021)
Choices regarding how signs are displayed in schools send messages regarding the status of languages and speakers of those languages. The monolingual paradigm can be implicitly reified by the position, shape, color, etc. of languages in relation to English on school signage (Author & Co-author, 2018). This can have a negative impact for culturally and linguistically diverse youth. In combining critical race media literacy with linguistic landscape research, we uncover a hidden media of raciolinguistic ideologies (Alim, 2016), and confront the hegemony found on some of the most overlooked and under questioned representations of media - signs in schools.